Antioxidant status of serum bilirubin, uric acid and albumin in pemphigus vulgaris. (1st March 2018) - Li, W. C.; Mo, L. J.; Shi, X.; Lin, Z. Y.; Li, Y. Y.; Yang, Z.; Wu, C. L.; Li, X. H.; Luo, Y. Z.; Qin, L. Q.; Mo, W. N.
Summary: Background: Oxidative stress and low antioxidant status are implicated in the pathogenesis of inflammatory and autoimmune diseases. Pemphigus vulgaris (PV) is an extremely severe autoimmune bullous dermatosis characterized by intraepithelial bullae on the skin and mucosa, and its antioxidant status is not fully understood. Aim: To assess correlations between PV and serum antioxidant levels of bilirubin, uric acid (UA) and albumin. Methods: We enrolled 116 patients newly diagnosed with PV who were admitted to the First Affiliated Hospital of Guangxi Medical University (Guangxi, China), and 108 healthy controls (HCs). Clinical characteristics and laboratory parameters of patients were retrospectively analysed. Results: Our survey shows that compared with the HC groups, serum levels of bilirubin [total bilirubin (Tbil), direct bilirubin (Dbil) and indirect bilirubin (Ibil)], UA and albumin were significantly lower in patients with PV, regardless of sex. In all groups, serum Tbil, Dbil, Ibil, UA and albumin levels were lower for women than for men. Severity of pemphigus was slightly negatively associated with Tbil, Dbil and Ibil, but was not associated with UA or albumin. Moreover, when the data were adjusted for the covariances of age and sex separately, Tbil, Dbil, Ibil, UA and albumin were all relevant to PV. Conclusions: Our findings demonstrate that serum levels of bilirubin (Tbil, Dbil and Ibil), UA and albumin are reduced in patients with PV supporting the hypothesis that oxidative stress and antioxidant status are important in the pathogenic mechanism of PV.